Quantitative analysis of hemocyte morphological abnormalities associated with Campoletis sonorensis parasitization - Turnbull, Matthew W. (University of Arizona Library, 2004)
Endoparasitoids of arthropods evoke host cellular immune responses that result in hemocytic encapsulation of the endoparasitoid, unless these responses are disrupted by the parasite. Our interest has focused on mutualistic viruses found in some hymenopteran endoparasitoids that disrupt hemocyte function and prevent encapsulation. Specifically, the Campoletis sonorensis polydnavirus interacts with wasp factors to suppress immunity via expression of intracellular and secreted viral proteins. To study the roles of specific parasitization-associated factors on immunocyte morphology, fluorescence microscopy was used to visualize the actin cytoskeleton in infected and uninfected cells, or after treatment with C. sonorensis ovarian proteins or plasma from infected larvae. The titer and distribution of F- and G-actin were altered in hemocytes from parasitized insects relative to control cells, with plasma from parasitized larvae having an intermediate effect. This suggests that intracellular and secreted factors contribute to suppression of cellular immune responses in C. sonorensis. Abbreviation / CsIV: Campoletis sonorensis ichnovirus CsOPs: Campoletis sonorensis ovarian proteins FITC: fluorescein isothiocyanate